Anti-Forgery Document Detection System (FDDS) - Rassem, Taha H.; Makbol, Nasrin M.; Alsewari, Abdulrahman A.; Mohammed, Mohammed Falah; Kamal Z., Zamli (2018)
Image processing tools have been associated with a variety of crimes, including counterfeiting of currency notes, cheques, as well as manipulation of important government documents, wills, financial deeds or educational certificates.